Perancangan Aplikasi Katalog Museum Dengan Menerapkan Algoritma Zhutakaoka(Studi Kasus : Museum Negeri Provinsi Sumatra Utara - Fitri Yani Dalimunthe (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Abstract−The museum catalog makes it very easy for people to see a list of some of the information presented, the catalog can be said as an information medium that contains a list of collections in a museum so that people can find out the catalog they are looking for. String matching uses the Zhutakaoka Algorithm to match the pattern to be searched from the meaning of the catalog, so that the match in the pattern selection can be seen. It is hoped that the Zhutakaoka Algorithm can complete the matching in the search for the museum catalog, so that it can help the public in searching for the museum catalog.